CLASSIFICATION PACKAGED UNIT LOADS - , А. С., Л. В. (Municipal economy of cities (Technical science), 2013)
The analysis of existing classifications on properties packaged unit loads (TSHV). Analyzed the expansion of criteria with which to classify TSHV.